The Regional Development Agency in the Knowledge Economy: Boundary Crossing for Innovation Systems - Phil Cooke (European Regional Science Association (ERSA), 2003)
The rise of the Knowledge Economy has posed an extra and very significant problem for regional development agencies. Formed as the 'Industrial Age' was coming to an end, as instruments to help restructure old industrial regions, they now find the inward investment that once created new job opportunities disappearing to Central and Eastern Europe, North Africa, China and other low wage regions. This comes on top of the more general effects of Globalisation and the demand that regions should demonstrate greater Entrepreneurship. These three forces have caused crisis conditions for Regional Development Agencies (RDAs), but perhaps the rise of the Knowledge Economy has finally begun to make some realise that they require a radical overhaul if they are to justify continuance of their existence. This is also compounded by strengthening views that 'the market' is a better investnment and jobs allocator than public servants. An innovative case of institutional re-invention of an established RDA will be presented. The case in question is a classic Industrial Age RDA that has seen over 30,000 job losses in high tech manufacturing during the first years of the 21st Century. This shock caused re-thinking of role and strategy at the highest levels and the exploration and implementation of a model for 'Managing International Knowledge Flows'. Several innovative 'knowledge transfer' mechanisms have been put in place or mooted. Some have already shown sucess in stimulating more knowledge intensive production and services from established and new businesses. There are tensions in conducting change management of the kind to be described, and these are identified and commented upon. However the lessons from this early instance of reconfiguring a public RDA to face and interact innovatively with the Knowledge Economy are that success can be achieved, while the prospect of remaining unchanged seems increasingly to be possible economic and institutional oblivion.
Keywords: 330